Sosiologi Lembaga Pendidikan Islam Swasta: Studi Reproduksi Kelas Sosial dan Pembentukan Habitus Islami di SMA ZIIS Cilongok - Queen Qonita; Muh. Hanif (LP2M STIT Palapa Nusantara, 2026)
Pondok Pesantren Modern ZIIS (Zamzam Integrated Islamic School) Cilongok, Banyumas, Central Java, is an integrated Islamic educational institution that promotes Islamic and national values through the motto A Great Place to Learn. This study aims to analyze parents’ school choice patterns in relation to cultural and social capital, the mechanisms for forming students’ Islamic habitus through an integrated curriculum and co-curricular programs, and the dynamics of social reproduction within the ZIIS environment. This study used a qualitative approach with a case study design, strengthened by structured questionnaire data from four parents of Grade XI students during the 2024–2026 period. The results showed three main findings. First, parents’ school choice patterns were economically heterogeneous, including families with monthly incomes below IDR 1,000,000 to above IDR 6,000,000, but homogeneous in value orientation because all parents prioritized the formation of Islamic character, independence, and a protected social environment. Second, ZIIS consistently formed students’ Islamic habitus through a structured yaumiyah schedule, a tahfidz Al-Qur’an program, gradual entrepreneurship, and international language programs integrated into the official curriculum. Third, unlike urban elite Islamic boarding schools, ZIIS demonstrated relatively inclusive dynamics of social reproduction, marked by open access across economic classes, although three of the four parents recommended adding scholarship programs to make accessibility more equitable. The conclusion of this study emphasizes that ZIIS functions as a space for forming a modern Islamic habitus that integrates piety, independence, and global competitiveness with broader social reach than urban elite Islamic boarding schools. The implications of this study expand understanding of the role of private Islamic educational institutions in shaping students’ character while opening access to education across social classes.